SURAU WITHOUT BUYA: Authority and the Shifting Foundations of Minangkabau Cultural Life in Indonesia - Febri Yulika; Iswandi Syahputra; Azhari Akmal Tarigan; Benny Ridwan; Fatahuddin Aziz Siregar (State Islamic University North Sumatra, 2026)
This study examines the shifting role of the surau within Minangkabau society in West Sumatra, where it once functioned as a central institution for worship, learning, and the moral formation of young men. Traditionally anchored in the authority of the buya, the surau embodied a living synthesis of Islamic teaching and customary values. Drawing on field-based research, including in-depth interviews with religious scholars, customary leaders, and cultural experts, this study traces a significant transformation in its contemporary meaning. The findings suggest that the gradual detachment of the surau from the figure of the buya has eroded its philosophical and cultural significance, reducing it to a largely symbolic or physical space. This shift is closely linked to the diversification of Islamic educational orientations and the growing influence of local political dynamics. As a result, the surau no longer operates as a formative cultural institution, raising broader questions about continuity, authority, and identity in Minangkabau society.